Transcriptomic analysis of EJ28 bladder cancer cells persistently infected with Newcastle disease virus - Chan, Lee Chin (2018)
Newcastle disease virus (NDV) is a highly contagious avian virus which leads to tremendous economy loss in poultry industry. Nevertheless, NDV shows good oncolytic activities on cancer cells by inducing apoptosis and therefore, it has been assessed in clinical trials for cancer treatment. Despite their promising potential, NDV was found to be able to persistently infect cancer cells in vitro without causing any cell death. The morphological characteristics of the cancer cells persistently infected by NDV has been described in the previous studies but the exact mechanism involved has yet to be elucidated. Hence, the objective of this study is to investigate the transcriptomic profiles of cancer cells persistently infected by NDV. By challenging with three rounds of infection with Malaysian velogenic strain AF2240, the NDV persistently infected bladder cancer cells EJ28 was established and was designated as EJ28P. The persistency of EJ28P was confirmed when they have grown to 4-fold of the original seeding number after 5 days post NDV infection; whilst its parental cells was nearly diminished in the same condition. Annexin V apoptosis assay revealed that approximately 60% of parental cells underwent apoptosis at 48 h post infection while the EJ28P was about 30%, which was insignificantly different from mock-infection. EJ28P reinfected with recombinant NDV AF2240 with green fluorescent protein (rAF-GFP) exhibited green fluorescent even after 25 passages. This further confirmed the persistency of NDV in EJ28P. Subsequently, total RNA of EJ28 and EJ28P were extracted and subjected to microarray analyses. A total of 355 genes, which were differentially expressed in EJ28P compared to EJ28, were identified using edgeR program, with their log2 fold change of 2 or more. Among them, 222 genes were up-regulated while 133 genes were down-regulated. Gene ontology (GO) of these genes were obtained using PANTHER Classification System and Database for annotation, visualisation and Integrated Discovery (DAVID). Genes associated to cytokine and apoptosis such as IL6, IL8, GBP2, CXCL8, HER5 and TNF were down-regulated. Pathway analysis revealed that TGF-β signalling was downregulated in EJ28P, which could lead suppression of apoptotic pathway and promotion of cell proliferation. However, the anti-virus responses of EJ28P were not completely suppressed as interferon-induced transmembrane (IFITM1), an anti-viral protein gene was up-regulated. On the other hand, genes associated to solute carrier families that are responsible for glucose and amino acids transportation across the membrane, were significantly up-regulated, suggesting that high demand of energy for virus activities or for the cancer cell’s metabolism, or for both. In addition, genes related to keratin group were overexpressed possibly involved in maintaining the cell structural integrity. Since these expressed genes were not only beneficial to cell but also to virus, it may either reflect a competition on both cell and virus for each survival, or an interaction from both sides in order to maintain a co-existing form. Based on these analyses, it is postulated that impairment of apoptosis and defective in pro-inflammatory response, together with over expression of solute carrier families and keratin groups, contribute to NDV persistent infection in bladder cancer cells. This study expands our understanding on persistent NDV infection in bladder cancer cells.